PESANTREN KILAT RAMADHAN UNTUK MENINGKATKAN PENGAMALAN AGAMA REMAJA MESJID GABUNGAN 7 DESA KEC. KOTABULUH, KABUPATEN KARO - Hidayah, Nurul; Azis, Abdul; v, Rukmana; Jannah, Fathul (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2024)
This community service is entitled "Ramadhan Lightning Islamic Boarding School for Teenagers Combined Mosque of 7 Villages (Amburidi, Rih Tengah, T. Marahe, Ujung Deleng, Liang Merdeka, Negeri Ginger and Bandar Meriah) District. Buluh City, Karo Regency.” The purpose of this community service activity is 1) Want to know the religious understanding of the Adolescents of the Subdistrict Association. Buluh City, Kab. Karo, 2) Want to know the role of Islamic boarding schools in increasing the religious practice of teenagers in the Combined District. Buluh city, district. Karo. The benefit of this activity is that it is an alternative that can be implemented to increase religious understanding for teenagers in mosques in the district. Bulu City and its surroundings. The method used is a). Lecture, b). Questions and Answers, c). Demonstration. The results of the community service program are 1) By implementing the Ramadhan express Islamic boarding school, it can increase the religious understanding of combined youth in the district. Buluh City, district. Karo. 2) Islamic boarding schools are effective in increasing the religious practice of teenagers in the Combined District. Buluh city, district. Karo.